Economic analysis of pressurized chemical looping combustion for steam assisted gravity drainage applications. (November 2019) - Cabello, Arturo; Hughes, Robin W.; Symonds, Robert T.; Champagne, Scott; Lu, Dennis Y.; Mostafavi, Ehsan; Mahinpey, Nader
Highlights: A comprehensive techno-economic analysis of PCLC technology has been performed. The main contribution regarding CAPEX corresponded to the rotating equipment. Natural gas price and CAPEX largely affected the profitability of the CLC process. Operating at pressurized conditions was beneficial from an economic point of view. PCLC can be a competitive CO2 capture option for its use in SAGD facilities. Abstract: A great effort is still pending in terms of thorough bottom-up economic assessments in the particular case of Chemical Looping Combustion (CLC) and Pressurized Chemical Looping Combustion (PCLC) processes. This work tries to reduce this knowledge gap through a comprehensive techno-economic analysis of PCLC technology focused on the replacement of a Once-through Steam Generator (OTSG) for the production of steam in a Steam Assisted Gravity Drainage (SAGD) facility in Alberta (Canada) by a PCLC system that burns natural gas using ilmenite as oxygen carrier. The evaluation of capital expenditure (CAPEX) for the different CLC cases analyzed revealed that the main contribution to costs stemmed from the rotating equipment. The economic performance of the CLC processes was evaluated through the Levelized Cost of Steam (LCOS) and the cost of CO2 captured. These parameters ranged between 30.45 and 39.93 CAD/t of steam (23.61–30.95 USD/t) and between 44.39 and 107.05 CAD/t of CO2 (34.41–82.98 USD/t), respectively. In the particular case of the CLC unit that operated at atmospheric pressure, the results were 34.92 CAD/t of steam (27.07 USD/t) and 75.46 CAD/t of CO2 (58.50 USD/t), which highlighted the economic benefits resulting from the use of CLC technology under pressurized conditions. Finally, comparing the economic results obtained in this framework with those found in the literature using other Carbon Capture and Storage (CCS) technologies, it can be concluded that PCLC technology has the potential to be a competitive CO2 capture option in the future for use in industrial SAGD facilities.